Investment Risk Management Strategies in Sukuk: A Sharia Management Perspective - Judijanto, Loso (Sharia Business Management Department of STEBIS Bina Mandiri, 2024)
This study aims to analyze investment risk management strategies in sukuk instruments from a sharia management perspective. Sukuk, as a financial instrument that complies with sharia principles, has become an increasingly popular investment alternative in the global market, but also faces challenges in terms of risk management. Therefore, this study identifies and evaluates risk management strategies applied in sukuk investment, focusing on the sharia principles underlying the instrument. The research method used is a descriptive qualitative approach, involving literature studies and in-depth interviews with sharia finance experts and sukuk market practitioners. The analysis was conducted to identify the types of risks faced by sukuk investors, including market risk, credit risk, liquidity risk, and sharia compliance risk. The application of the principle of prudence and transparency in sukuk contracts can increase investor confidence and maintain the sustainability of the sukuk market. In conclusion, risk management in sukuk investment requires a careful approach and is based on strong sharia principles. The right risk mitigation strategy can help minimize potential losses and ensure that sukuk investments remain in accordance with sharia objectives, as well as providing sustainable benefits to investors and society..